2023
DOI: 10.1152/physrev.00048.2021
|View full text |Cite
|
Sign up to set email alerts
|

Cortical-subcortical interactions in goal-directed behavior

Abstract: Flexibly selecting appropriate actions in response to complex, ever-changing environments requires both cortical and subcortical regions, which are typically described as participating in a strict hierarchy. In this traditional view, highly specialized subcortical circuits allow for efficient responses to salient stimuli, at the cost of adaptability and context-specificity, which are attributed to the neocortex. Their interactions are often described as the cortex providing top-down command signals for subcort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 405 publications
1
9
0
Order By: Relevance
“…In models of inhibitory control, pre-SMA and striatum (including caudate) play a role in the downstream selection of a competing action among a space of possible action programs. The dorsal striatum is uniquely situated as the inter-face between cortex and the rest of the basal ganglia, forming part of an indirect cortico-basal ganglia-thalamic loop involved in action selection [100]. In a study of adults with ADHD, Sebastian and colleagues [105] found less activation in right caudate for people with ADHD compared to control participants, which is in line with what we report here.…”
Section: Direct Group Comparisons Yielded Activity Differences In Bra...supporting
confidence: 90%
See 2 more Smart Citations
“…In models of inhibitory control, pre-SMA and striatum (including caudate) play a role in the downstream selection of a competing action among a space of possible action programs. The dorsal striatum is uniquely situated as the inter-face between cortex and the rest of the basal ganglia, forming part of an indirect cortico-basal ganglia-thalamic loop involved in action selection [100]. In a study of adults with ADHD, Sebastian and colleagues [105] found less activation in right caudate for people with ADHD compared to control participants, which is in line with what we report here.…”
Section: Direct Group Comparisons Yielded Activity Differences In Bra...supporting
confidence: 90%
“…In addition to the lateral cortical regions, we also observed group differences in the bilateral caudate and medial frontal cortical regions, including the anterior cingulate and pre-SMA. These regions are crucial nodes in the neural system involved in stopping behaviors, such as the ability to withhold a response in the K-CPT [100, 85, 101, 102, 103, 96, 104]. In models of inhibitory control, pre-SMA and striatum (including caudate) play a role in the downstream selection of a competing action among a space of possible action programs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But this needs to be done in a way that still supports fast simulations of large-scale models, so that training of these models for specific computational tasks remains computationally feasible. In addition, the computational role of projections to and synaptic inputs from subcortical areas, such as basal ganglia and the thalamus (see [Cruz et al, 2023] for a recent review), needs to be modeled and analyzed through integrated large-scale models. Altogether, this work is likely to complement, challenge, and enhance experimental work in vivo that aims at clarifying the organization of brain computations.…”
Section: Discussionmentioning
confidence: 99%
“…3). These results suggest that motor cortex funnels information from behaviorally-relevant cortical computations -e.g., about environmental events or working memory processes -to subcortical motor circuits, making them integral to executing complex flexible behaviors 11,18,20,25,63,64 . From an evolutionary perspective this makes sense: rather than duplicating or reinventing the robust and effective control functions of subcortical systems, motor cortex can provide an adaptive advantage by orchestrating downstream controllers based on information uniquely available to it.…”
Section: Discussionmentioning
confidence: 99%